WEBGIS-BASED ONLINE MULTI-HAZARD COASTAL MAPPING IN DEMAK REGENCY, INDONESIA - Harjayanti Nasfa Isyfa'lana; Muhammad Abraham Haris Pramudya Teja Sakti; Arief Laila Nugraha; Moehammad Awaluddin; Fauzi Janu Amarrohman (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2026)
Demak Regency is a coastal area along the northern coast of Java that is increasingly exposed to environmental pressure from natural processes and human activities, resulting in coastal multi-hazards. Previous studies have mainly focused on single-hazard assessments and have not sufficiently integrated a multi-hazard approach. This study applies the Coastal Hazard Wheel (CHW) 3.0 method to identify coastal multi-hazard levels in Demak Regency and presents the results through an interactive WebGIS platform. The WebGIS system is developed as a single portal using ArcGIS Experience Builder. The system consists of a Home page built with ArcGIS StoryMap providing an overview of the study area and methodology, an Interactive Map using ArcGIS Web Map for spatial visualization of coastal multi-hazard distribution, a Dashboard presenting statistical information in graphical form, and a Usability Testing module using ArcGIS Survey123 to evaluate user experience. Evaluation was conducted through program testing and usability testing. Results indicate that all system functions operate properly across smartphones, laptops, and multiple web browsers without functional errors. Usability evaluation produced an average score of 4.66, categorized as excellent. The integration of CHW 3.0 and WebGIS is expected to support effective identification, visualization, and management of coastal multi-hazards in Demak Regency.